A QUASI-TEACHING EXPERIMENT STUDY ON IMPROVING CRITICAL THINKING ABILITY IN ENGLISH READING AMONG SENIOR HIGH SCHOOL STUDENTS IN CHINA - Wen Jia; Nor Hazwani Munirah Lateh, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study tries to explore the possibility of improving critical thinking ability in English reading among senior high school students in China. The mixed research method is adopted in this research. The reading teaching technique IRAES is shaped. An 8-week teaching intervention is conducted in a Chinese senior high school. 50 students from the experimental class and 50 students from the control class are selected to participate in the quasi-teaching experiment. The reading comprehension part of English test of national college entrance examination will be used as the instrument to collect the quantitative data. A semi-structured interview outlines will be used to collect qualitative data. 2 students from the experimental class and 2 English teachers from the senior high schools are selected as the interviewees to get the qualitative data. The research results show the students’ critical thinking ability can be improved in English reading teaching by using the IRAES reading teaching technique. Both students and teachers state a positive attitude towards the teaching intervention with the IRAES reading teaching technique.